A new species and new records of Gymnolaelaps Berlese from Iran (Acari: Laelapidae), with a review of the species occurring in the Western Palaearctic Region - Joharchi, Omid; Halliday, Bruce (Zootaxa, 2013)
This paper reports on five species of mites of the genus Gymnolaelaps associated with ants and soil in Iran—G. artavilensis sp. nov. from Pheidole pallidula, G. laevis (Michael) and G. myrmecophilus (Berlese) from Tetramorium caespitum, G. myrmophila (Michael) from Formica sp., and G. obscuroides Costa from soil. Gymnolaelaps australicus Womersley and G. hospes (Berlese) have also been reported from Iran, in association with P. pallidula, but those records are incorrect. A key to the species of Gymnolaelaps occurring in the Western Palaearctic Region is presented. We review the related genus Laelaspisella Marais & Loots, and transfer Gymnolaelaps kabitae Bhattacharyya and G. canestrinii (Berlese) sensu Costa to Laelaspisella.